SHUANGJINGZI MIDDLE TRIASSIC SYN-COLLISIONAL CRUST-DERIVED GRANITE IN THE EAST INNER MONGOLIA AND ITS CONSTRAINT ON THE TIMING OF COLLISION BETWEEN SIBERIAN AND SINO-KOREAN PALEO-PLATES - Li J.Y.; Gao L.M.; Sun G.H.; Li Y.P.; Wang Y.B. (My University, 2007)
The Shuangjingzi granite intruded the Late Paleozoic accretion-collisional complex, which is exposed in the north of Xar Moron River, eastern Inner Mongolia. This pluton underwent the intensively ductile deformation during the Mesozoic, and is characterized by occurrence of muscovite in mineral assemblage, high SiO2, Al2O3 and alkaline content, low Na2O/K2O ratio (<1), higher A/CNK (1.02 - 1.08) and A/NK (1.20 - 1.35) ratios, light REE enrichment with weak Eu anomalies, depleted Ti and Sc, especially depleted Nb and Ta but enriched Th, higher 143Nd/144Nd (0.512229 - 0.512286) and (143Nd/144Nd)i (0.512068-0.512199) ratios, lower εNd(t) (- 2.71 - - 5.28) values with younger Nd depleted mande model ages (1000 - 1300Ma), higher 87Sr/86Sr (0.7135161 - 0.722096) and (87Sr/86Sr)i(0.705756 - 0.709187) ratios in petro-chemistry, indicating that this pluton is crust-derived, probably mainly come from the re-melting of Paleozoic accretion-collisional complexes and older continental margins. SHRIMP U-Pb dating of zircons from two samples of this granite yields apparent ages of 229.2 ± 4.1Ma and 237.2 ± 2.7Ma, indicating the occurrence of this pluton in the Middle Triassic. Available geological data make us get conclusions that the collision along the Xar Moron suture between Siberian and Sino-Korean paleo-plates began at middle Permian (about 270Ma), and ended in the middle Triassic, which led uplifting of a huge EW-extended mountain from Beishan eastwards through southern Inner Mongolia to central Jilin during the early to middle Triassic, and that the Late Triassic magmatic activities in the area occurred in the extensional setting in the late stage of tectonic evolution of the mountain, implying the beginning of a new stage of the crustal evolution of the area.
Keywords: CRUST-DRIVED; EAST INNER MONGOLIA; SHUANGJINGZI TWO-MICA GRANITE; TRIASSIC; XAR MORON SUTURE; Mesozoic::Triassic; Мезозой::Триасовая